1993
DOI: 10.1200/jco.1993.11.10.1957
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal palliation of chemoresistant ovarian cancer: three consecutive phase II trials of the Mid-Atlantic Oncology Program.

Abstract: Antiestrogen therapy may offer the possibility of useful and, occasionally, long-term palliation of refractory epithelial ovarian carcinoma, with little toxicity. There may be a trend toward a dose-response effect, which represents a suitable topic for a future prospective trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 64 publications
3
46
0
Order By: Relevance
“…The response rate in patients with chemoresistant ovarian carcinoma treated with tamoxifen (20 mg day-') is 7% (Ahlgren et al, 1993). Thus, the responses, initially to bryostatin 1 and subsequently to tamoxifen, seen in these patients, although anecdotal, were unexpected and prompted this investigation into combining these agents.…”
Section: Discussionmentioning
confidence: 99%
“…The response rate in patients with chemoresistant ovarian carcinoma treated with tamoxifen (20 mg day-') is 7% (Ahlgren et al, 1993). Thus, the responses, initially to bryostatin 1 and subsequently to tamoxifen, seen in these patients, although anecdotal, were unexpected and prompted this investigation into combining these agents.…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of primary ovarian tumors express ERs (26), the efficacy of endocrine therapies has not been adequately evaluated in ovarian cancer. Clinical studies of tamoxifen in a small number of chemoresistant ovarian cancer patients have demonstrated that a small subset of unselected patients responds to tamoxifen treatment (26)(27)(28). However, a recent study has demonstrated that preselection of ovarian cancer patients according to ER status results in a significantly higher percentage of patients responding to antihormonal therapy (29).…”
Section: Hoxb13 Abrogates the Antagonistic Effect Of Tamoxifenmentioning
confidence: 92%
“…trials of palliative chemotherapy in small-cell lung cancer (James et al, 1996) and hormonal palliation of ovarian cancer (Ahlgren et al, 1993)]. In other reported trials, palliation is defined as the treatment given to prevent medical conditions arising [e.g.…”
mentioning
confidence: 99%